Preventive treatment alternatives in pediatric patients with autism spectrum disorder in the dental practice. Literature review - Valdez-Zambrano, Vianca E. (2024)
Autism comes from the Greek word auto, which means "self." Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social interaction and communication. Dental treatment in patients with ASD can be challenging due to their behavior. Therefore, this review discusses preventive treatment techniques for pediatric patients with ASD at the dental office, as the prevalence of children with autism is growing. Thus, dentists would face more patients with autism in their daily practice. Regarding treatment protocols, they would require specialized attention in dental management. Information was searched in the following databases: PubMed, SciELO, Redalyc, Elsevier, and the International Association of Paediatric Dentistry (IAPD). The descriptors used were: Pediatric Dentistry, Autism, ASD, Autism Spectrum Disorder, and Management of the autistic patient.